Incarcerated People Living with HIV: A Qualitative Exploration of Stigma - Smoyer, Amy B; Ferris, Shannon; Earnshaw, Valerie A (Health & Social Work, 2022)
Thousands of people living with HIV are incarcerated in the United States. Research about this vulnerable community has focused on access and adherence to medical care, including the impact of stigma on these treatment outcomes. This study presents qualitative data collected from 18 incarcerated and formerly incarcerated men and women living with HIV to expand knowledge about how HIV stigma shapes the lived experience of incarceration. The HIV Stigma Framework, including theory about enacted, anticipated, and internalized stigma, was used to analyze participants’ narratives. Findings demonstrate an ongoing struggle with all three of these stigma mechanisms. Most participants deliberately concealed their HIV status and, therefore, experienced little enacted stigma. However, their narratives do describe anticipated stigma and, to a lesser extent, internalized stigma. There were gender differences in HIV disclosure and symbolic stigma and intersectionality are used to understand this variation. These findings illustrate the persistence of HIV stigma in correctional institutions and underscore the importance of fighting HIV stigma and homophobia within social work practice.
Keywords: dept.swk

Stress, Marginalization, and Disruption: A Qualitative Rapid Situational Assessment of Substance Users and HIV Risk in Lebanon - Khoshnood, Kaveh; Smoyer, Amy B.; Maviglia, Francesca; Kara, Janine; Khouri, Danielle; Fouad, Fouad M.; Heimer, Robert (International Journal of Environmental Research and Public Health, 2022)
Lebanon is a diverse and dynamic nation of six million people that has experienced considerable disruption for the last two decades. The Syrian Civil War, which began in 2011, resulted in the displacement of 1.1 million Syrians to Lebanon. Today, Lebanon is the country with the largest per capita number of refugees in the world. In addition, the country experienced a social, economic, and political crisis in 2019 that destabilized the entire society-circumstances that were further complicated by COVID-19 pandemic. With all of the competing calamities in Lebanon, there has been limited scientific investigation into substance use and the risk of HIV infection among the country's population. To address this gap in knowledge, a qualitative rapid situational assessment (RSA) of substance use and risk of HIV infection in and around Beirut, the nation's capital, was conducted. The goal of this analysis is to describe the demographics and drug use patterns of this population, explore their HIV knowledge and risks, and build knowledge about their perceptions of and access to substance use treatment and other social services.
Keywords: COVID-19; Drug Users; HIV Infections; HIV risk; Health Services Accessibility; Humans; Lebanon; Pandemics; Refugees; Stress, Psychological; Substance-Related Disorders; dept.swk; peer-reviewed; rapid situational assessment; refugees; substance use